2015
DOI: 10.1007/s00432-015-1957-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anemia is associated with adverse outcome in patients with urothelial carcinoma of the bladder following radical cystectomy

Abstract: PA is significantly associated with worse oncological outcome in patients undergoing RC. Based on the additional unfavorable influence of blood transfusion, this emphasizes the importance of early diagnosis and correction of anemia and implementation of alternative methods of blood volume management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
1
22
1
1
Order By: Relevance
“…A meta-analysis (33) performed in 2014 highlights the role of C-reactive protein in the outcome of urological neoplasms with a negative impact on RFS and OS. In Gierth et al's (34) 2015 study, the investigators reported that preoperative anemia in patients with BC who underwent RC worsened the prognosis for the outcome of the disease. Limitations of this study include its retrospective nature; however, we followed patients for almost 10 years after TURBT.…”
Section: Fig 3 Overall Survival Estimates Of 54 Patients With Pta Bmentioning
confidence: 99%
“…A meta-analysis (33) performed in 2014 highlights the role of C-reactive protein in the outcome of urological neoplasms with a negative impact on RFS and OS. In Gierth et al's (34) 2015 study, the investigators reported that preoperative anemia in patients with BC who underwent RC worsened the prognosis for the outcome of the disease. Limitations of this study include its retrospective nature; however, we followed patients for almost 10 years after TURBT.…”
Section: Fig 3 Overall Survival Estimates Of 54 Patients With Pta Bmentioning
confidence: 99%
“…In one study of 684 patients undergoing radical cystectomy, preoperative anemia was found to be an independent predictor of disease recurrence, cancer-specific mortality, and all-cause mortality [57]. Of note, this study showed that although perioperative blood transfusion significantly increased all-cause mortality independent of preoperative anemia, those with preoperative anemia who received perioperative blood transfusion had no significant difference in outcome measures.…”
Section: Preoperative Interventionmentioning
confidence: 82%
“…Of note, this study showed that although perioperative blood transfusion significantly increased all-cause mortality independent of preoperative anemia, those with preoperative anemia who received perioperative blood transfusion had no significant difference in outcome measures. The authors suggest that correction of preoperative anemia may have a survival benefit irrespective of reducing transfusion rate [57]. Preoperative anemia has also been found to be an independent predictor of cancer-specific mortality for patients undergoing radical nephrectomy [48] and nephroureterectomy [49] .…”
Section: Preoperative Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various predictive models have been widely studied to reduce BC-related death (Lammers et al, 2015). Previous studies have attempted to identify variables that have prognostic value in patients with T2 to T4 stage BC undergoing cystectomy, one of which was pretreatment hemoglobin (Hb) level (Thrasher et al, 1994;Gierth et al, 2015;Milojevic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%